2017
DOI: 10.21621/sajms.2017111.04
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Stock and the Sovereign CDS markets: A panel VAR based analysis

Abstract: This study explores the relationship between the Stock and the Sovereign Credit Default Swaps (SCDS) markets by using dataset of 36 countries.We apply Panel Vector Autoregressive (PVAR) model to gauge the impact of one market's shocks to the other. Our results decipher that changes in stock market returns explain the significant portion of the SCDS market spreads' changes. Furthermore, the magnitude of this explanation is linked with the volatility of the SCDS market. These analyses indicate that the firsthand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…There is also evidence that the stock market return is significantly related to CDS spread changes (Ngene, Hassan, and Alam, 2014;Tabak, Miranda, and Medeiros, 2016). By employing the Panel VAR methodology, Shear and Butt (2017) investigated the CDS market for 36 countries. They found that a significant portion of the CDS spread changes are explained by stock market return.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also evidence that the stock market return is significantly related to CDS spread changes (Ngene, Hassan, and Alam, 2014;Tabak, Miranda, and Medeiros, 2016). By employing the Panel VAR methodology, Shear and Butt (2017) investigated the CDS market for 36 countries. They found that a significant portion of the CDS spread changes are explained by stock market return.…”
Section: Literature Reviewmentioning
confidence: 99%